215k views
1 vote
-4х + 9y = 9
x - Зу = -6

User Stloc
by
5.3k points

2 Answers

6 votes

Answer: x = 9 y = 5

Step-by-step explanation: I like to use elimination for problems like these. Start by multiplying everything in the second equation (x - 3y = -6) by 4. Your equation should then look like this: 4x - 12y = -24

Now add the two equations as if they were two numbers:

-4x + 9y = 9

4x - 12y = -24

Your x's will cancel out and 9y + -12y = -3y and 9 + -24 = -15. This will make your new equation look like:

-3y = -15

Divide both sides by -3 and you get that y = 5

Substitute 5 in for y for any of the original given equations and solve:

-4x + 9y = 9

-4x + 9(5) = 9

-4x + 45 = 9

-4x = -36

x = 9

User Henry Tseng
by
5.8k points
4 votes

Answer:

x= 9 y = 5, your welcome

User Robbert Van Elk
by
5.7k points